Fatal Clostridium sporogenes Soft Tissue Polymicrobial Infections in Two Immunocompetent Cases: Case Report - Chaudhary, Preeti; Gulati, Neelam; Gupta, Varsha; Dhanda, Gazal; Kumar, Mani Bhushan; Sharma, Swati; Goel, Anku; Kumar Attri, Ashok (Infectious Disorders - Drug Targets, 2023)
Background: Clostridium sporogenes is reported rarely in literature. Reports from the skin and soft tissue infections are even less, more so in immunocompetent patients. Case Presentation: Two skin and soft tissue infections with C. sporogenes in immunocompetent patients have been presented in this study. One of the cases was following an electrical burn wound, and the other was following a bedsore. Both patients expired despite antibacterial treatment and debridement. Discussion and Conclusion: C. sporogenes had usually been reported after trauma particularly after penetrating and deep wound infection. More attention should be given to these patients so that the infection can be treated and diagnosed early in suspected anaerobic infections like Clostridium species.
Keywords: Clostridium sporogenes